CircGLIS3 Promotes High-Grade Glioma Invasion via Modulating Ezrin Phosphorylation - Yan Li (Frontiers in Cell and Developmental Biology, 2021)
High-grade glioma is highly invasive and malignant, resistant to combined therapies, and easy to relapse. A better understanding of circular RNA (circRNA) biological function in high-grade glioma might contribute to the therapeutic efficacy. Here, a circRNA merely upregulated in high-grade glioma, circGLIS3 (hsa_circ_0002874, originating from exon 2 of GLIS3), was validated by microarray and Real-time quantitative reverse transcription PCR (qRT-PCR). The role of circGLIS3 in glioma was assessed by functional experiments both in vitro and in vivo. Fluorescence in situ hybridization (FISH), RNA pull-down, RNA immunoprecipitation (RIP), and immunohistochemical staining were performed for mechanistic study. Cocultured brain endothelial cells with glioma explored the role of exosome-derived circGLIS3 in the glioma microenvironment. We found that upregulation of circGLIS3 promoted glioma cell migration and invasion and showed aggressive characteristics in tumor-bearing mice. Mechanistically, we found that circGLIS3 could promote the Ezrin T567 phosphorylation level. Moreover, circGLIS3 could be excreted by glioma through exosomes and induced endothelial cell angiogenesis. Our findings indicate that circGLIS3 is upregulated in high-grade glioma and contributes to the invasion and angiogenesis of glioma via modulating Ezrin T567 phosphorylation.